Becoming-Body: Embodiment and Affect Experience - Ramos, Ana (2024)
This article discusses the aesthetics of being. It posits the experience of having/being a body as a perceptive-event. Working from the example of the yogic pose tadasana, it explores the idea of the body as a site of pulsation of immanent movements. It understands the articulation of these movements through William James’ concept of consciousness, but with an added distinction between affective-consciousness and reflexive-consciousness. By fostering a complex approach beyond the subject-object basic structure, it highlights the primacy of relation. This dynamic approach to subjectivity goes beyond an anthropocentric view of the subject as it considers the event as its own becoming-subject. It argues strongly for the reality of affect and asks how we perceive affect. Perceptive-events perform a self-organization of the virtual tendencies present in the relational field. This sheds light on the invisible processes immanently supporting experience’s inherent multiplicity.